Is Combined Bulevirtide and Pegylated Interferon Therapy for Chronic Hepatitis D Superior over Bulevirtide Monotherapy? - V. E. Syutkin; A. O. Bueverov; P. O. Bogomolov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Bulevirtide is a novel antiviral agent approved for suppression of chronic hepatitis D but requiring further research into optimising the treatment scheme.Aim. Comparative assessment of bulevirtide monotherapy versus combined treatment with bulevirtide and pegylat-ed interferon (PEG-IFN) using published trial data.Key points. MYR201 and MYR203 trials expose a higher frequency of HBsAg and HDV RNA extinction, as well as more effective HDV suppression for combined bulevirtide/PEG-IFN therapy compared to bulevirtide monotherapy.Conclusion. Combined bulevirtide/PEG-IFN therapy has particular advantages over bulevirtide monotherapy in patients with chronic hepatitis D. Further research is required to optimise bulevirtide dosage and duration of therapy.